New strategies for effective treatment of vitamin K antagonist‐associated bleeding. (June 2015) - Yates, S. G.; Sarode, R.
Summary: Vitamin K antagonists have been used as oral anticoagulants in the treatment and prevention of thromboembolic events for over half a century. Although vitamin K antagonists are effective in the management of thromboembolic events, the need for routine monitoring and the associated risk of bleeding has resulted in the development and licensing of direct oral anticoagulants for specific clinical indications. Despite these developments, vitamin K antagonists remain the oral anticoagulants of choice in many clinical conditions. Severe bleeding associated with oral anticoagulation requires urgent reversal. Several options for the reversal of vitamin K antagonist exist, including vitamin K, prothrombin complex concentrates and plasma. In this manuscript, we review current evidence and provide physicians with treatment strategies for more effective management of vitamin K antagonist‐associated bleeding.